PERAN ORANG TUA SEBAGAI SUMBER PENDIDIKAN KARAKTER BAGI ANAK USIA DINI - M. Rezki Andhika (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
This paper examines the role of parents as a source of character education for early childhood. This study was conducted using the library research method. The results of this study indicate that the role of parents is a determining factor for children's development, both physically and mentally, is the role of both parents as the first and main educators for children who are born until they are adults. In the process of forming knowledge, various parenting styles conveyed by parents are very important. Education in the family plays a very important role in developing the character, personality, cultural values, religious and moral values ​​, and simple skills of children. The role of parents in influencing the character of children is no longer borne by the mother only. The role of the father in shaping the character of the child is very large. Fathers are still obliged to participate in maintaining interactions with their children, such as inviting them to talk, joke, and play.